How ideas move : theories and models of translation in organizations - Scheuer, John Damm (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book builds on research in translation studies of change in organizations and demonstrates the implications and application of these findings for managing innovation and change. When implementing ideas into practice in order to carry out innovative change, translation is key. From strategic and leadership changes to policy and health management decisions, abstract ideas such as "LEAN", "CSR","Sustainability", "Public-Private Partnerships","Clinical Pathways" and "AI" are introduced to improve organizational processes. However, in any company and organization, miscommunication and misinterpretation can lead to these ideas being modified, added to and appropriated in ways that makes them unsuccessful. This book presents a case for change ideas in organizations being translated rather than "implemented" and offers a profound understanding of the translation processes needed in order for this to succeed. This vital study is a must-read for researchers, students and practitioners including change agents, general and health care managers, public servants as well as strategic managers and policy-decision-makers"--
OCLC-licensed vendor bibliographic record.
Keywords: Organizational change; Technological innovations; Communication in management; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Interest; BUSINESS & ECONOMICS / Management